Helicopter‐based immobilization of moose using butorphanol–azaperone–medetomidine. (6th July 2022) - Levine, Rebecca L.; Dwinnell, Samantha P. H.; Kroger, Bart; Class, Corey; Monteith, Kevin L.
Abstract: Chemical immobilization is an important tool for the capture, study, and management of wildlife. Increased regulation of traditional opioids has necessitated a search for alternative drugs in wildlife capture. Butorphanol–azaperone–medetomidine (BAM) is one promising alternative that has been used in a range of taxa, though often on medium‐size mammals using ground‐based methods. We tested the efficacy of BAM via remote delivery from a helicopter in a wild population of moose ( Alces alces shirasi ) in northwestern Wyoming. In March 2020 and 2021, we immobilized male ( n  = 15) and female ( n  = 26) moose with butorphanol (0.20 mg/kg), azaperone (0.066 mg/kg), and medetomidine (0.079 mg/kg), with antagonists atipamezole (0.495–0.527 mg/kg) and naltrexone (0.124–0.151 mg/kg) to reverse immobilizations. Mean induction (x̄ ± SE; 9.2 ± 0.6 min) and mean recovery times (7.2 ± 0.5 min) were longer but still comparable to published instances of moose captured using traditional chemical immobilizers (carfentanil, etorphine, thiafentanil). All animals survived >60 days post‐capture. Our findings add to a body of work demonstrating that BAM provides rapid inductions, reliable sedation, and quick reversals in a variety of taxa and by aerial remote delivery. Abstract : We assessed the efficacy of butorphanol–azaperone–medetomidine via remote delivery from a helicopter in a wild population of moose ( Alces alces shirasi ). Moose had brief inductions and recoveries, were unresponsive during handling, and had high rates of post‐capture survival. Butorphanol‐azaperone‐medetomidine is accessible to researchers and managers, has low toxicity to humans, and provided induction quality comparable to conventional immobilizers for a wild ungulate population.